Mimpi Besar Abdullah Sa’id Dalam Pengembangan Pendidikan Islam Di Indonesia - Jaya Saputra; Hilalludin Hilalludin; Adi Haironi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education has an important role in shaping individual character and advancing the nation. This research highlights the contribution of K.H. Abdullah Sa'id in the development of Islamic education in Indonesia, especially through the establishment of the Hidayatullah Islamic Boarding School. The aim of this research is to identify the vision, approach and impact produced by K.H. Abdullah Sa'id in improving the quality of Islamic education. The research method used is literature study, with analysis of literature from various relevant sources. Research findings show that K.H. Abdullah Sa'id succeeded in integrating Islamic values ​​with modern knowledge, improving the quality of teaching staff, and creating inclusive programs such as scholarships and community empowerment. Its innovative and inclusive approach not only improves the quality of education but also strengthens the moral and spiritual foundations of students. The implications of this research underscore the importance of adopting the educational principles of K.H. Abdullah Sa'id to create an education system that is more holistic and responsive to the demands of the times. Further research is recommended to explore the long-term impact of this educational model and its potential for application in other educational institutions.